THE EXPRESSION OF RELIGIOUS MODERATION IN LOMBOK AS NEGOTIATION STRATEGY IN INTERFAITH ENGAGEMENT THROUGH THE TOPAT WAR - Nensia, Nensia; Simbolon, Subandri; Israpil, Israpil (Al-Qalam, 2024)
While wars generally have negative implications and bring chaos, Topat War in Lingsar Village, West Lombok Regency, is an exception. Despite being called a war, this annual tradition is carried out joyfully and without the intention of hurting each other. Instead of using weapons or battling against each other, the Balinese-Hindus and the Sasak-Muslims throw food, called ketupat, at each other. This uniqueness creates curiosity about how two-different religions celebrate the same tradition with mutual understanding. Therefore, this research will look at the prerequisites for successful interfaith engagement reflected in Perang Topat. This research was conducted qualitatively with meta-analysis approach to find a variety of scientific documents as primary data. The results showed that the series of religious rituals were carried out together while faithfully upholding their respective beliefs. It refers to the internum and externum aspects that live in this society, which are the essence of religious moderation. Furthermore, the win-win solution for both religions, the "mutual" process, the accommodation process of understanding and agreement in the annual rituals are designed to maintain the memory of the importance of living in harmony with people of different religions and traditions. The decision-making and ways of preserving the sustainability show a commitment to nationality, tolerance, non-violence, accommodation to local culture, and respect for minorities without exclusivity which are indicators of moderation. Thus, moderate religious attitudes are needed as a negotiation strategy to create an effective and harmonious atmosphere between religious communities.